Digital Leadership, Quality of Work Life, and Work Productivity: A Systematic Literature Review - Siti Zulaikha; Murnia Kala; Wiwi Winanda Nur; Satriadi (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
Digital transformation has changed leadership practices, employee work conditions, and productivity demands in organizations. This systematic literature review aims to synthesize studies on digital leadership, quality of work life and work productivity. The review followed PRISMA 2020. The literature search was conducted in January 2025 through three databases, namely Scopus, Google Scholar, and SINTA. English and Indonesian search strings were used to identify peer-reviewed journal articles released from 2019 to 2024. After identification, screening, eligibility, and inclusion, 16 articles were selected for thematic synthesis. The findings show that digital leadership supports work productivity through clearer communication, employee adaptation, innovation, and organizational support. Quality of work life also helps maintain employee wellbeing and productivity in digital work environments that may create technostress, digital fatigue, blurred work boundaries, and burnout. The synthesis indicates that the quality of work life can be understood as a potential linking mechanism between digital leadership and work productivity, although most reviewed studies have not directly tested mediation. This review contributes theoretically by integrating leadership capability, employee work conditions, and productivity into one analytical framework for understanding employee outcomes in digital transformation contexts